Effect of Levodopa Initiation on the Gut Microbiota in Parkinson's Disease - Palacios, Natalia; Hannoun, Anas; Flahive, Julie; Ward, Doyle; Goostrey, Kelsey; Deb, Anindita; Smith, Kara M. (Frontiers in Neurology, 2021)
Background: The impact of Levodopa on the gut microbiota of Parkinson’s disease (PD) patients has not been sufficiently addressed. Methods: We conducted a longitudinal study to examine the impact of Levodopa initiation on the gut microbiota composition of 19 PD patients who had not previously been exposed to Levodopa. Patients provided two stool samples prior to and two samples 90 days after starting Levodopa. Motor impairment (MDS-UPDRS Part III), diet, and other patient characteristics were assessed. 16S rRNA gene amplicon sequencing was used to characterize the microbiota. We examined, cross-sectionally and longitudinally, the associations between Levodopa use and alpha and beta diversity and performed feature-wise, multivariate modelling to identify taxa associated longitudinally with Levodopa use and with improvement in motor function after Levodopa administration. Results: We did not observe significant differences in alpha or beta diversity before vs. after initiation of Levodopa. In longitudinal feature-wise analyses, at the genus level, no taxa were significantly associated with Levodopa use after false discovery rate (FDR) correction (q<0.05). We observed a marginally lower relative abundance of bacteria belonging to Clostridium group IV in PD patients who experienced a medium or large improvement in motor impairment in response to Levodopa compared to those with a small response ( = -0.64 (SE: 0.18), p-trend: 0.00015 p-FDR: 0.019). Conclusions: In this study, Levodopa was not associated with changes in microbiota composition in this longitudinal analysis. The association between abundance of Clostridium group IV and short-term motor symptom response to Levodopa is preliminary and should be investigated in larger, longer-term studies, that include a control group.